Cognitive and social aspects of software developers nformation behavior: An analysis of the literature - De Souza, Leonardo Pereira Pinheiro [UNESP]; Valentim, Marta L'gia Pomim [UNESP]; Vila, Daniel Mart'nez [UNESP] (My University, 2019)
The software industry plays an important role in the Brazilian society as a profitable sector that employs hundreds of thousands of people. Programmers have special relevance in this context since they develop computational programs using knowledge and information. This literature review addresses the relationship of these professionals with information, i.e., their information behavior, as well as their needs and problems in this regard. We also emphasize the importance of contextualize the informational behavior in the social sphere, in this case, the organizational culture. We studied if the volume of the scientific production on the information behavior of these professionals in Information Science corresponds with the relevance of their profession to the society, compared to the production on the informational behavior of other knowledge professionals. As a methodology, we searched the papers on this subject indexed by online databases, analyzing their abstracts to verify the paradigms and approaches adopted. It is shown that few studies consider this subject in Information Science, revealing the need of more research on this topic.
Keywords: Computer Software; Information Needs; User Studies